Development of composites, reinforced by novel 3D woven orthogonal fabrics with enhanced auxeticity. (November 2019) - Khan, Muhammad I; Akram, Jehanzeb; Umair, Muhammad; Hamdani, Syed TA; Shaker, Khubab; Nawab, Yasir; Zeeshan, Muhammad
Auxetic materials are under great attention of researchers due to their excellent mechanical response under certain conditions. Previous works have been carried out in knitted or uni-stretch woven fabrics. In the present study, three-dimensional (3D) woven structures were produced and the effect of float length of ground weave and binding yarn on auxeticity of the fabric was investigated. Eight different 3D orthogonal woven structures/reinforcements were produced on rapier dobby loom by changing the float length in ground weave and binding yarns. Hand layup technique was used for composite fabrication, while green epoxy resin was used as a matrix. For investigating the auxeticity, 3D reinforcement samples were subjected to tensile loading and change in their thickness was measured. The results showed that 3D woven reinforcements with equal and maximum float length of ground weave and binding yarn showed greater auxetic behavior, because both weaves support each other and room for opening of structure increases. As the difference between the float length of ground weave and binding yarns increases, the auxeticity of reinforcement decreases because the ground weave and binding yarn cancel out the effect of each other. Moreover, the impact energy absorption of the developed composites was found to increase with the increase in float length, justifying that the structures are auxetic in nature.